Heterogeneous expectations and asset price dynamics - Noemi Schmitt (Bamberg University, Bamberg Economic Research Group (BERG), 2018)
Within the seminal asset-pricing model by Brock and Hommes (1998), heterogeneous boundedly rational agents choose between a fixed number of expectation rules to forecast asset prices. However, agents' heterogeneity is limited in the sense that they typically switch between a representative technical and a representative fundamental expectation rule. Here we generalize their framework by considering that all agents follow their own time-varying technical and fundamental expectation rules. Estimating our model using the method of simulated moments reveals that it is able to explain the statistical properties of the daily behavior of the S&P500 quite well. Moreover, our analysis reveals that heterogeneity is not only a realistic model property but clearly helps to explain the intricate dynamics of financial markets.
Keywords: C63; D84; G15; 330; financial markets; stylized facts; agent-based models; technical and fundamental analysis; heterogeneity and coordination